2020
DOI: 10.3389/fgene.2020.00263
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Alternative Single-Step GBLUP Approaches and Training Population Designs for Genomic Evaluation of Crossbred Animals

Abstract: As crossbreeding is extensively used in some livestock species, we aimed to evaluate the performance of single-step GBLUP (ssGBLUP) and weighted ssGBLUP (WssGBLUP) methods to predict Genomic Estimated Breeding Values (GEBVs) of crossbred animals. Different training population scenarios were evaluated: (SC1) ssGBLUP based on a single-trait model considering purebred and crossbred animals in a joint training population; (SC2) ssGBLUP based on a multiple-trait model to enable considering phenotypes recorded in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
(93 reference statements)
0
14
1
Order By: Relevance
“…A reason for these underestimated values in Duroc-ssGBLUP scenarios might be due to the used scaling factors (τ = 1 and ω = 1) to combine G −1 and matrices. Alvarenga et al (2020) indicated that optimization of scaling factors might be helpful for obtaining more unbiased values using ssGBLUP method ( Alvarenga et al, 2020 ). Another possible reason for these underestimated values in Duroc-ssGBLUP scenarios can be due to the preferential treatment to select elite pigs for genotyping in breeding companies.…”
Section: Resultsmentioning
confidence: 99%
“…A reason for these underestimated values in Duroc-ssGBLUP scenarios might be due to the used scaling factors (τ = 1 and ω = 1) to combine G −1 and matrices. Alvarenga et al (2020) indicated that optimization of scaling factors might be helpful for obtaining more unbiased values using ssGBLUP method ( Alvarenga et al, 2020 ). Another possible reason for these underestimated values in Duroc-ssGBLUP scenarios can be due to the preferential treatment to select elite pigs for genotyping in breeding companies.…”
Section: Resultsmentioning
confidence: 99%
“…Using tuning parameters to construct H matrix may be an alternative for bias reduction. However, the tuning parameters ( τ and ω ) do not have a specific ideal value; in other words, many parameters combination should be tested to find the best combination for the database (Alvarenga et al., 2020; Oliveira et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As for other difficult to measure traits, using genome-assisted breeding value prediction would be an interesting option (de Campos et al 2015). Different types of genomic evaluation models could be qualified, but most likely multitrait single-step models allowing the inclusion of information obtained in GWAS studies, adapted for crossbreeding, should be considered and studied (Alvarenga et al 2020;Misztal et al 2020). Therefore, the genetic and genomic evaluation of boar taint will need careful choices of traits, models, and methods, taking into account reported issues in order to allow performing a successful selection against boar taint.…”
Section: Genetic and Genomic Evaluationmentioning
confidence: 99%